Pronounce it perfectly in English - Yates, Jean (Hauppauge, New York : Barrons Educational Series, 2005)
This program emphasizes speaking, sound discrimination, and standard intonation patterns in American-style English
1. English vowel sounds -- 2. English consonant sounds -- 3. Stress patterns -- 4. Intonation patterns -- 5. Appendix
Author from book
Compact discs
Keywords: English language; English language -- Self-instruction; English language -- Audio-visual aids; English language -- Pronunciation; English language -- Pronunciation -- Problems, exercises, etc; English language -- Study and teaching; English language -- Study and teaching -- Foreign speakers